Atonement [videorecording (DVD)] - Wright, Joe, 1972-; Ronan, Saoirse, 1994-; McAvoy, James, 1979-; Knightley, Keira, 1985-; McEwan, Ian (Universal Studios Home Entertainment, 2008)
In 1935, 13-year-old fledgling writer Briony Tallis and her family live a life of wealth and privilege in their enormous mansion. On the warmest day of the year, the country estate takes on an unsettling hothouse atmosphere, stoking Briony's vivid imagination. Robbie Turner, the educated son of the family's housekeeper, carries a torch for Briony's headstrong older sister Cecilia. He hopes that Cecilia has comparable feelings. All it will take is one spark for this relationship to combust. When it does, Briony - who has a crush on Robbie - is compelled to interfere. She goes so far as to accuse Robbie of a crime he did not commit. Cecilia and Robbie declare their love for each other, but, ultimately, he is arrested. Briony bears false witness and the course of three lives is changed forever. As Briony grow older, she continues to seek forgiveness for her childhood misdeed.